Respuesta a la aplicación de extracto de Estevia (Stevia rebaudiania) en el rendimiento productivo de dos variedades de papa en el sector de Santa Martha de Cuba, provincia del Carchi - Cuaspud Velasco, Omar Edison (2015)
This research was conducted in the parish of Santa Martha de Cuba, Canton Tulcán, Carchi Province, north latitude 00040'00 "east longitude 77045'00" and altitude 2895 m The conditions presented by the place are average annual precipitation 1300 mm, 90.56 mm average monthly rainfall, average temperature 11 ° C and relative humidity 70-80%. The texture of sandy loam, pH: 6.5, and organic matter content is 6.7% with good drainage. In this research two varieties of potato Super Chola and Capiro were used, plus eight treatments, which were made of potato varieties and Stevia extract dose of 1.0 were studied; 1.5 and 2.0 cc / L applied from pre-flowering to maturity of the crop, with a frequency of 10 days, 3 months and an absolute witness without application Block design was used completely randomized (DBCA) in factorial arrangement A x B, and four replications, estimated for Factor A potato varieties and Factor B for doses of Stevia extract, subjecting the analysis variance with Tukey's test at the 95% statistical probability...........